Analysis of Semiconductor Circuits - Erkin Abduraimov ,Dilshod Khalmanov, Saidakhon Dusmukhamedova (International Journal of Advanced Science and Technology, 2020)
In article is considered questions of the theoretical analysis of thyristor and resistor circuit with use the characteristic of the thyristor and the load lines, and also transition processes in nоn-linеar dynamic circuits are considered. The solution for equations of a condition by digital method is offered. During wide progress of the electronic equipment, nonlinear resistive circuits are widely used in various areas of automatic equipment, radio electronics, computer facilities and power supply. Semiconductor thyristor circuits have two steady electrical statuses (opened and closed), has fast response time and can switch big load currents. The main thyristor property is the possibility of moment’s time delay opening in the presence on this forward voltage. This property of the thyristor allows creating devices with value regulation of voltage output. By means of a control current it is possible to control the moment of switching on the thyristor. Current in a switched on status of the thyristor proceeds also after removal of current of control. To disconnect an anode current and to recover the switched-off thyristor status, including it is possible by lowering of current in the semiconductor item below critical value. The way of thyristors's switching by current of the controlling electrode is a great importance. First, it allows turning on the thyristor at the expense of the control signal in different voltage anode values. Secondly, this way gives the possibility to switch big currents by the low-powered control signal.